Role of BRCA 1 и BRCA 2 gene mutations in the occurrence of male breast cancer - A. V. Bykova; I. K. Vorotnikov; Ya. V. Vishnevskaya; D. A. Denchik; L. N. Lyubchenko (Опухоли женской репродуктивной системы)
Particular emphasis has been recently placed on the mechanisms of carcinogenesis in breast cancer (BC), including those in male BC. The paper describes the major risk factors for BC in male patients and covers the role of BRCA1 and BRCA2 gene mutations in the occurrence of this pathology. The most important studies conducted in this area and their results are presented.